Dinickel(II) complexes with pyridine-substituted bis(triazolylmethyl)amine ligands: Structures and magnetic properties. (15th November 2020) - Inthong, Jeeranun; Nakarajouyphon, Vasut; Udomsasporn, Kwanchanok; Phomphrai, Khamphee; Yoshinari, Nobuto; Konno, Takumi; Sangtrirutnugul, Preeyanuch
Graphical abstract: The 2-pyridylmethyl substituents of bis(triazolylmethyl)amine ligands promote the bridging coordination mode of the 1, 2, 3-triazole moieties to produce the first crystallographically characterized dinickel-bis(triazolyl)amine complexes. Meanwhile, the chloride and nitrate ligands affect the structural arrangements and consequently the magnetic interactions between the Ni II centers. Highlights: Pyridyl-substituted bis(triazolyl)amines gave triazole-bridged dinickel(II) complexes. The auxiliary Cl − and NO3 − ions resulting in syn and anti isomers, respectively. Ni II ions of anti − [Ni2 (L2 )2 (NO3 )2 ][NO3 ]2 showed the strongest magnetic interactions. Abstract: The coordination behavior of the newly prepared bis(triazolylmethyl)amine-type ligands bis[(1- R -1 H -1, 2, 3-triazol-4-yl)methyl]amine [R = CH2 Ph (L1 ), CH2 -2-pyridyl (L2 )] and 1-(1-benzyl-1 H -1, 2, 3-triazol-4-yl)- N -((1-(pyridin-2-ylmethyl)-1 H -1, 2, 3-triazol-4-yl)methyl)methanamine (L3 ) toward Ni II ions was investigated. The reaction of NiCl2 ·6H2 O with the benzyl-substituted bis(triazolylmethyl)amine ligand L1 afforded the mononuclear Ni II complex Ni(L1 )2 Cl2 (1 ). On the other hand, dinuclear Ni II complexes, [Ni2 (L2 )2 Cl2 ]Cl2 (2 ) and [Ni2 (L3 )2 Cl2 ]Cl2 (3 ), were obtained when NiCl2 ·6H2 O was reacted with the pyridine-substituted ligands L2 and L3, respectively. Single-crystal X-ray analysis revealed that the two octahedral Ni II centers in 2 and 3 are bridged by two triazole rings through nitrogen donors to generate the dinuclear complexes with a syn arrangement. Meanwhile, treatment of Ni(NO3 )2 with L2 afforded the related dinickel(II) complex [Ni2 (L2 )2 (NO3 )2 ](NO3 )2 (2′ ), in which two non-bridging triazole rings and two nitrate ions are positioned in an anti arrangement. Complexes 2 and 3 showed antiferromagnetic coupling between the two Ni II centers ( S = 1), with J values following the trend: 2′ > 2 > 3 .